Surgical management of neovagina with amnion interposition in a urogynecology and pelvic floor unit: a case report - Torres, Kerima L. M.; Cabrales, Filiberto M.; Penilla, Luisa F. R.; Gonzales, Alejandro C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This is a case report of a 20-year-old patient, diagnosed since adolescence with Mullerian aplasia, referred to the urogynecology service of our institution to perform a vaginosplasty as part of her treatment for sexual restoration. This was done through a modification of McIndoe's surgical technique to create a neovagina using amniotic membranes as graft interposition tissue for the vaginal mold. With a satisfactory surgical follow-up obtaining the objective of an anatomically functional vagina. The modified McIndoe surgical technique using amnion is a viable option and it should be considered in those institutions that have access to this tissue.